Peranan Pendidik dalam Pembelajaran Daring pada Anak Usia Dini di Masa Pandemi Covid-19 di Kecamatan Sleman - Affifah, Noor Rokhmah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2021)
Currently the world's population is being shocked by the corona virus or commonly known as COVID-19. Educators as the main element in formal education have an important role and are encouraged to adapt to the implementation of learning that originally used conventional face-to-face methods and switched to online learning. The type of research used is qualitative research in the form of observation and interviews. The purpose of this study was to describe the role of teachers in online learning (on the network) for early childhood during the Covid-19 pandemic in Sleman District. The roles of teachers are still carried out so that students remain controlled and directed in learning. The teacher's role is very important in teaching and learning activities. In this pandemic period, teachers must always be responsive when students do not understand what the teacher is saying in online learning with applications that do not involve direct face-to-face and provide solutions so that learning goes well and smoothly.